PENGUATAN KOMPETENSI PENGELOLA DESA WISATA MELALUI PELATIHAN PELAYANAN PRIMA DI DESA WISATA BANTARAAGUNG - Muhammad Abdul Ghoni; Joel Faruk Sofyan; Arian Zikri; Ina Sawitri; Irman Ramdhan Fauzi (POLITEKNIK LP3I JAKARTA, 2026)
This Community Service Program (Pengabdian kepada Masyarakat/PkM) aimed to enhance the competencies of human resources managing the Bantaragung Tourism Village, Majalengka, through service excellence training. The main problems faced by the partners included limited understanding of professional tourism services, inadequate communication skills with tourists, and the lack of optimal service orientation toward visitor satisfaction. The implementation method employed a participatory approach through observation, needs identification, training sessions, service simulations (role play), interactive discussions, and mentoring activities. The training materials covered the concepts of service excellence, tourism service ethics, effective communication, tourist complaint handling, and the development of professional attitudes in tourism services. The results of the program indicated improvements in participants’ knowledge, skills, and awareness regarding the importance of service quality in supporting tourism village development. Participants demonstrated enhanced communication skills, better service attitudes, and improved understanding of professional and tourist-friendly service standards. The program also increased the motivation of tourism village managers to consistently implement excellent service practices in daily tourism activities. With the improvement of human resource competencies, Bantaragung Tourism Village is expected to provide better tourism experiences for visitors and support the development of competitive and sustainable community-based tourism.